Pemetaan Infrastruktur Pengelolaan Sampah Berbasis Masyarakat (PSBM) Menggunakan Sistem Informasi Geografis (SIG) dengan Wilayah Studi di Kabupaten Sleman, Yogyakarta: Indonesia - Satria, Muhammad Rifqi; Putra, Hijrah Purnama; Wacano, Dhandhun; Yuriandala, Yebi (Asian Journal of Innovation and Entrepreneurship, 2026)
The population growth in Sleman Regency has led to an increase in waste generation, necessitating an effective and participatory management system. This study aims to map the distribution of Community-Based Waste Management (CBWM) infrastructure, such as TPS3R, waste banks, and "waste donation" programs, and to evaluate their distribution and effectiveness using Geographic Information Systems (GIS). A descriptive quantitative method with a spatial approach was employed using QGIS software. Data analysis utilized overlay, buffering, and nearest neighbor analysis to evaluate the spatial service coverage. The results indicate a significant surge in the number of facilities, rising from 234 units in 2022 to 508 units in 2025; however, the distribution remains uneven. Population density significantly influences this distribution, where Ngaglik District, with the highest density (202 people/ha), still possesses a sub-optimal facility ratio compared to other regions. This study recommends spatial evidence-based priority zoning, including the establishment of a 500-meter service buffer in densely populated settlements and the revitalization of inactive units. These mapping results are expected to serve as a framework for more measurable and sustainable policy-making and evaluation of waste management in Sleman Regency